All-optical closed-loop voltage clamp for precise control of muscles and neurons in live animals - Bergs, Amelie; Liewald, Jana F.; Rodriguez-Rozada, Silvia; Liu, Qiang; Wirt, Christin; Bessel, Artur; Zeitzschel, Nadja; Durmaz, Hilal; Nozownik, Adrianna; Dill, Holger; Jospin, Maëlle; Vierock, Johannes; et al. (Nature Communications, 2023)
Excitable cells can be stimulated or inhibited by optogenetics. Since optogenetic actuation regimes are often static, neurons and circuits can quickly adapt, allowing perturbation, but not true control. Hence, we established an optogenetic voltage-clamp (OVC). The voltage-indicator QuasAr2 provides information for fast, closed-loop optical feedback to the bidirectional optogenetic actuator BiPOLES. Voltage-dependent fluorescence is held within tight margins, thus clamping the cell to distinct potentials. We established the OVC in muscles and neurons of Caenorhabditis elegans, and transferred it to rat hippocampal neurons in slice culture. Fluorescence signals were calibrated to electrically measured potentials, and wavelengths to currents, enabling to determine optical I/V-relationships. The OVC reports on homeostatically altered cellular physiology in mutants and on Ca2+-channel properties, and can dynamically clamp spiking in C. elegans. Combining non-invasive imaging with control capabilities of electrophysiology, the OVC facilitates high-throughput, contact-less electrophysiology in individual cells and paves the way for true optogenetic control in behaving animals.